The influence of low pH on in vitro growth and biochemical parameters of Plantago almogravensis and P. algarbiensis - Martins, Neusa (2013)
The effects of low medium pH (4.50, 5.00 and 5.75) on in vitro growth and on several biochemical parameters (lipid peroxidation, proline and carbohydrate content, antioxidant enzymes activities and total soluble protein) of Plantago almogravensis and P. algarbiensis micropropagated shoots were investigated. Overall, it was observed that medium pH did not affect in vitro proliferation and rooting. Interestingly, cultures of both species modify the initial pH value to the same final value. Results have shown that the lowest pH tested induced an increase in the level of lipid peroxidation in roots of both species and in shoots of P. algarbiensis, indicating plasma membrane damage. An accumulation of carbohydrates was observed in roots of P. almogravensis cultured in pH 4.50 and 5.00. It was observed a slight response of the enzymatic system to medium pH, particularly in P. almogravensis. Based on the results obtained we can conclude that Plantago species are apt to grow in vitro in medium with pH values much lower than the usually used in tissue culture, which is in agreement with the fact that both species colonize acid soils.